Gripper configuration and control design on omnidirectional mobile manipulator arm - Auni Zahidah, Mohd Rasol (2022)
An articulated robotic arm is made up of links that connect a series of rotating joints to an end effector. This project will enhance the function of3-DoF robotic arm. The present Omnidirectional Manipulator System (OMSys) has been successfully constructed and implemented by the former students who were in charge of this project. However, it is not incomplete. The first issue to address is to be an arm with pick-and-place function, a grasper/gripper was added at the end effector. Second is, to control the end effector together with mecanum and 3DoF arm. Therefore, modified current code for arm, mecanum, and grasper, along with Remote configuration, is the solution for controlling the arm and vehicle movement. The Expected result are forecasted result. There are two expected outcomes that have been predicted for this project. First, the expected result for this project is establish the grasper/gripper configuration on the OMSys arm manipulator for pick-and-place operation. Second, to design a control system for the end effetor of the grasper/gripper. This result can be achieved by combine both mecanum and its manipulator arm. Next, all the motor are connected to Arduino board containing programming codes that can remotely control both mecanum and its manipulator.